1989
DOI: 10.1159/000132745
|View full text |Cite
|
Sign up to set email alerts
|

Regional assignment of the human loci for uvomorulin (UVO) and chymotrypsinogen B (CTRB) with the help of two overlapping deletions on the long arm of chromosome 16

Abstract: Using cDNA probes for the human uvomorulin (UVO) and rat chymotrypsinogen B (CTRB) genes, we have analyzed two overlapping interstitial deletions on human chromosome 16q by Southern blot analysis. One deletion, with breakpoints at 16q22.1 and 16q22.3, results in loss of the UVO locus The second deletion, whose breakpoints are at 16q22.1 and 16q23.2, leads to loss of the CTRB locus. Therefore, UVO resides between both proximal deletion breakpoints within band 16q22.1 whereas CTRB is located between both distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
4

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 8 publications
0
41
0
4
Order By: Relevance
“…The human E-cadherin gene has been mapped to chromosome 16q22.1 (Mansouri et al, 1988;Natt et al, 1989). Its expression was reduced in several types of human carcinomas (Shimoyama et al, 1991;Bussemakers et al, 1992;Inoue et al, 1992;Umbas et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The human E-cadherin gene has been mapped to chromosome 16q22.1 (Mansouri et al, 1988;Natt et al, 1989). Its expression was reduced in several types of human carcinomas (Shimoyama et al, 1991;Bussemakers et al, 1992;Inoue et al, 1992;Umbas et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…These correl ative findings are highly suggestive of an important role of E-cadherin in preventing the transition to tumorous and/or invasive growth. Even more intriguing is the possibility that the human E-cadherin gene located at 16q22.1 (Natt et al, 1989) may correspond to a TSG identified by loss of heterozygosity in this genetic region in hepatocellular, breast, and prostate car cinomas (Carter et al, 1990;Sato et al, 1990;Tsuda et al, 1990;Zhang et al, 1990). If E-cadherin plays an important role in tumor suppression, the fa t locus may provide a useful model system for investigating the mechanism of this effect.…”
Section: Hyperplastic Overgrowth Mutants Fat: a Tsg Encoding A Putatimentioning
confidence: 99%
“…1 E-cadherin was suggested to act as an invasion and metastasis suppressor since its loss in benign tumors could lead to a rapid progression into invasive, metastatic carcinomas. 2 CDH1 was mapped to the chromosome region 16q22.1, 3 which shows frequent allelic imbalance in a variety of tumors and is believed to harbor a tumor-suppressor gene. Mutation analysis of the coding region has been carried out in endometrial and ovarian carcinomas, 4 thyroid, 5 prostate, 6 bladder, 7 colorectal, 8 gastric, 9 breast 10 -14 and colon cancer, 15 but frequent CDH1 mutations were only found in diffuse gastric and infiltrative lobular breast carcinomas.…”
mentioning
confidence: 99%